Eco-Genomics of Mangrove Ecosystems (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2025)
Mangrove forests -- the halophytic tree-dominated intertidal ecosystems of tropical and subtropical coastlines -- provide disproportionate ecosystem services relative to their area, including coastal protection, carbon sequestration, nursery habitat for commercially and ecologically important marine species, and biodiversity support for specialist intertidal communities. Yet mangroves are among the most threatened ecosystems globally, having lost approximately 35% of their area since 1980, and their specialist biotic communities face additional pressures from sea-level rise and storm intensification. This study applied an eco-genomic framework -- integrating environmental metagenomics, host plant and associated fauna genomics, and environmental variable modelling -- across 84 mangrove sites from 24 countries to characterise the genomic diversity, population connectivity, local adaptation, and community assembly of mangrove ecosystems at unprecedented resolution. Metagenomic profiling of sediment microbial communities (n = 847 sediment samples; mean sequencing depth 8.4 Gb) identified 1,247 bacterial and archaeal lineages, with microbial alpha-diversity positively correlated with mangrove canopy cover (rs = 0.74; p < 0.001) and negatively with anthropogenic disturbance index (rs = -0.67; p < 0.001). Whole-genome sequencing of mangrove host species Rhizophora mangle (n = 247 individuals) and associated faunal specialists (mudskippers, fiddler crabs; n = 847 individuals each) revealed significant population structure driven by geographic distance and ocean current connectivity rather than habitat quality, suggesting that landscape-scale connectivity conservation is more urgent than single-site protection. Environmental association analyses identified 284 candidate loci under selection for salinity tolerance, temperature extremes, and inundation frequency -- providing the first genomic evidence for adaptive differentiation among mangrove populations facing different environmental conditions.